A production systems study on Ramcar Technology Incorporated - Herce, Cynee Rachel E. (College of Engineering, 1997)
The system under study Ramcar Technology Incorporated, or RamTech, is of a job-shop type. It makes custom molds, dies, and special made to order equipment. However, it specializes in plastic injection molds. Most of its products have cycle times ranging from as short as three days to six months. Being a newly formed company (started in 1988), the system is currently facing the problems of managing day-to-day activities of production planning, scheduling and inventories. Furthermore, the system's make-to-order environment makes such tasks more complicated than its counterparts in mass production types. The group employed a total systems approach in analyzing the current problems faced by the company. However, the groups' efforts focused on the problems directly related to the production planning function. Among the significant drawbacks of the current planning system is the forecasting method in use. The horizon is too short to be of significant aid in long range strategic capacity planning. The recommendations of the group included the adoption of Focus Forecasting to remedy the said drawback. Based on the forecasted demand, a Capacity and Aggregate plan was developed. These formed the basis for recommending that the system adopt a production plan which uses up all the overtime hours available before buying machines or hiring additional moldmakers or EDM operators.